An experimental study to test the efficacy of Mesenchymal Stem Cells in reducing corneal scarring in an ex-vivo organ culture model. (January 2020) - Rose, Jeyanth Suresh; Lalgudi, Sharmili; Joshua, Aarwin; Paul, Joshua; Thambaiah, Augustine; Wankhar, Syrpailyne; Chacko, Geeta; Kuriakose, Thomas; Korah, Sanita
Abstract: In this study, we evaluated the effect of placenta-derived Mesenchymal Stem Cells (MSCs) versus placebo in improving corneal transparency following experimental injury in an ex-vivo organ culture model of post-mortem human corneas. We also compared the influence of MSCs on the basic histopathology of the cornea and the immunohistochemistry markers of fibrotic corneal scarring. Mesenchymal Stem Cells extracted from the placenta were isolated and expanded in-vitro. Five pairs of post-mortem human corneas harvested for the corneal transplant of equal grade were included in the study. Corneas of the same pair were randomly assigned to either the case arm or the control arm. All corneas underwent a standardized superficial keratectomy, 4 mm in diameter. The case and control arm corneas received an intrastromal injection of MSCs and placebo respectively. The corneal button was maintained in an organ culture system for 28 days under the standard protocol. Laser light was passed through the corneas mounted on a self-styled modified artificial anterior chamber. Image analysis was used to quantify corneal transparency. Haematoxylin & Eosin staining and Immunohistochemistry was done for Alpha SMA (Smooth Muscle Actin). Laser scatter measurements were measured using Image Analysis (Image J Software). The difference in the mean of Full-Width Half Maximum (FWHM), Max intensity and Red pixel intensity between the cases and the controls was 101.5, 16.3 and 11.4 respectively which was found to be statistically significant (P < 0.05). Histopathology showed a disorganized Bowman's layer in the controls as compared to the cases. Alpha Smooth Muscle Actin at the injury site stained 3 + in all controls as compared to 1 + in the cases, showing a statistically significant difference (p = 0.005). Based on our findings, we consider that placenta-derived Mesenchymal Stem Cells can alter evolving corneal scarring into a more favourable outcome with better corneal transparency and lesser fibrotic corneal scarring. Highlights: Mesenchymal Stem Cells show reduced corneal scarring. Corneal transparency increases significantly with Mesenchymal Stem Cells. Histopathological staining shows marked difference between cases and controls.